Transformasi Tabuh Rah Menjadi Tajen Di Desa Adat Batur Rening Kecamatan Abiansemal Kabupaten Badung Propinsi Bali: Kajian Teologi Hindu - I Ketut Gunarta (Jayapangus Press, 2019)
Tabuh rah is the sowing of blood as a ritual for the implementation of bhuta yajña. Blood is a liquid that is used as a means of balancing the bhuana agung and the bhuana alit. The ceremony in the Patur Penataran Agung Batur Rening was held for 11 days as an aci-aci. In addition, this activity was carried out as a feeling of gratitude and to strengthen the brotherhood between communities. In line with the implementation of the piodalan, the community filled in the blanks by doing tajen at the temple jaba sisi. People assume that every chicken is a tajen because they have blood droplets. So that by labeling tabuh rah the community can safely carry out tajen. The concept of belief in the existence of supernatural beings gives rise to beliefs about Godhead, in Hinduism this concept is called Hindu theology which is contained in the tabuh rah ceremony. Pasupati God is Lord Shiva or his hybrid term is Ratu Gede Bebotoh or Sang Hyang Rare Angon as Bhatara Guru uses the tabuh rah as a medium to invite humans to live the game of chicken fight not to make it as babotoh, but as a person who sided with the authority.